Proceedings of the 22nd ACM International Conference on Information &Amp; Knowledge Management 2013
DOI: 10.1145/2505515.2505692
|View full text |Cite
|
Sign up to set email alerts
|

Building optimal information systems automatically

Abstract: Software frameworks which support integration and scaling of text analysis algorithms make it possible to build complex, high performance information systems for information extraction, information retrieval, and question answering; IBM's Watson is a prominent example. As the complexity and scaling of information systems become ever greater, it is much more challenging to effectively and efficiently determine which toolkits, algorithms, knowledge bases or other resources should be integrated into an informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…This allowed precise automatic evaluation and more effective error analysis, leading to the development of high-performance QA incorporating hundreds of different strategies in real time (IBM Watson) (Ferrucci et al 2010). The OAQA approach was also used to evaluate and optimize several multi-strategy QA systems, some of which achieved state-of-the-art performance on the TREC Genomics datasets (2006 and 2007) (Yang et al 2013) and BioASQ tasks (2015-2018) (Chandu et al 2017;Yang et al 2015Yang et al , 2016.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This allowed precise automatic evaluation and more effective error analysis, leading to the development of high-performance QA incorporating hundreds of different strategies in real time (IBM Watson) (Ferrucci et al 2010). The OAQA approach was also used to evaluate and optimize several multi-strategy QA systems, some of which achieved state-of-the-art performance on the TREC Genomics datasets (2006 and 2007) (Yang et al 2013) and BioASQ tasks (2015-2018) (Chandu et al 2017;Yang et al 2015Yang et al , 2016.…”
Section: Resultsmentioning
confidence: 99%
“…Using the Configuration Space Exploration techniques described in the previous subsection (Garduño et al 2013), a group of researchers at CMU were able to automatically identify a system configuration which signficantly outperformed published baselines for the TREC Genomics task (Yang et al 2013). Subsequent work showed that it was possible to build high-performance QA systems by applying this optimization approach to an ensemble of subsystems, for the related set of tasks in the BioASQ challenge (Yang et al 2015).…”
Section: Component Evaluation For Biomedical Qamentioning
confidence: 99%